Pengaruh Return On Equity (ROE), Return On Assets (ROA) Dan Net Profit Margin (NPM) Terhadap Harga Saham PT Handjaja Mandala Sampoerna (HMSP) Tbk. Tahun 2011-2020 - Josua Parlinggoman Pangaribuan; Raya Panjaitan; Nancy Nopeline (LPPM Universitas HKBP Nommensen, 2022)
This study aims to determine the effect of Return On Equity (X1), Return On Assets (X2), and Net Profit Margin (X3) to Stock Price (Y) at PT Handjaja Mandala Sampoerna (HMSP) Tbk. Year 2011-2020. Population in this study are the financial statements of PT Handjaja Mandala Sampoerna (HMSP) Tbk. and the sampling of 40 in this study is financial statements of PT Handjaja Mandala Sampoerna (HMSP) Tbk. quarterly from 2011-2020. Based on the results of multiple linear regression test the regression equation obtained is Y = 3411.421 – 13.683X1 – 15.000X2 + 65.210X3 + e. Based on the results of the partial test, it was found that the variable Return On Equity has a significant effect on Stock Prices, Return On Assets does not significant effect on the Stock Price, While the Net Profit Margin significant effect on Stock Prices. Simultaneous test results it is known that Return On Equity, Return On Assets, and Net Profit Margin do not significant effect on Stock Prices. R Square value in research this is 0.146 which means the ability of the independent variable to explain the dependent variable is 14.6%. The remaining 85.4% is influenced by the variable other than this research model.